The isotope effect on divertor conditions and neutral pumping in horizontal divertor configurations in JET-ILW Ohmic plasmas. (August 2017) - Uljanovs, J.; Groth, M.; Jaervinen, A.E.; Moulton, D.; Brix, M.; Corrigan, G.; Drewelow, P.; Guillemaut, C.; Harting, D.; Simpson, J.; Huber, A.; Jachmich, S.; et al.
Highlights: The neutral dynamics within the divertor is significantly affected by the fuelling isotope mass. A decrease in neutral throughput in the corner configuration was observed to occur during the onset of the ionization front withdrawal out of the LFS corner. The higher susceptibility of the sub-divertor pressures to the proximity of the LFS strike-point to the pumping plenum for deuterium is contrary to previous understanding of the isotope effect on divertor conditions. Abstract: Understanding the impact of isotope mass and divertor configuration on the divertor conditions and neutral pressures is critical for predicting the performance of the ITER divertor in DT operation. To address this need, ohmically heated hydrogen and deuterium plasma experiments were conducted in JET with the ITER-like wall in varying divertor configurations. In this study, these plasmas are simulated with EDGE2D-EIRENE outfitted with a sub-divertor model, to predict the neutral pressures in the plenum with similar fashion to the experiments. EDGE2D-EIRENE predictions show that the increased isotope mass results in up to a 25% increase in peak electron densities and 15% increase in peak ion saturation current at the outer target in deuterium when compared to hydrogen for all horizontal divertor configurations. Indicating that a change from hydrogen to deuterium as main fuel decreases the neutral mean free path, leading to higher neutral density in the divertor. Consequently, this mechanism also leads to higher neutral pressures in the sub-divertor. The experimental data provided by the hydrogen and deuterium ohmic discharges shows that closer proximity of the outer strike point to the pumping plenum results in a higher neutral pressure in the sub-divertor. The diaphragm capacitance gauge pressure measurements show that a two to three-fold increase in sub-divertor pressure was achieved in the corner and nearby horizontal configurations compared to the far-horizontal configurations, likely due to ballistic transport (with respect to the plasma facing components) of the neutrals into the sub-divertor. The corner divertor configuration also indicates that a neutral expansion occurs during detachment, resulting in a sub-divertor neutral density plateau as a function of upstream density at the outer-mid plane.